An Industrial systems design study on Luzon Bakers Corp. - Gabriel, Randee Almond; Latonio, Patrick Gerard; Mangoba, Dianne Mayumi; Sandejas, Ana Maria (College of Engineering, 2001)
Luzon Bakers Corp is a bakery located in Tabang, Guiguinto, Bulacan which started its operations last 04 June 1998. It is a manufacturer of various bread, pastries, and cake products. The bakery operates on a 1250 square meter warehouse. It started off with seventeen employees, and now has sixty-two among the different departments. This paper is an industrial systems design study performed on the Luzon Bakers Corp so as to observe and analyze its supply chain management techniques and strategies. Section 3 completely and accurately documents each of the supply chain components of the company, namely Purchasing, Inventory Management, Raw Materials Warehousing, Manufacturing, Finished Goods Warehousing, Transport Operations, and Customer Service Operations. For each component, the documentation focused on the various policies, strategies, key performance indicators, and its basic operating processes. Section 4 identifies the potential problem areas for each of these components. This problem identification is followed by an in-depth analysis in Section 5. This section identifies the interrelationships between the problem areas, using a streamline analysis, and determines the gravity of the problem's effect on the operations of the company, using a rating system. The major problem areas of Luzon Bakers Corp were found to be: 1) incomplete or incorrect key performance indicators (for Purchasing, Inventory Management, Warehousing, Transport Operations, and Customer Service Operation); 2) the inexistence of a supplier evaluation; 3) an improper implementation of the stock locator system in the warehouse; 4) the lack of storage equipment; and 5) the inexistence of a transport provider. Given these problem areas, Section 6 generates different alternatives problem solutions. These alternatives were evaluated based on a rating system customized for each problem. The alternatives which proved best were presented in the succeeding section. Finally, Section 7 provides a thorough discussion of the recommendations to the company. This is accompanied by an implementation program for the company to guide it in the proper execution of recommendations.